Individual and collective strategies for the management of hygiene and cleaning services in the hemodialysis sector of a macro-regional reference hospital (Research, Society and Development, 2021)
Hemodialysis sectors are places of high complexity of treatments and work activities, present high demand of workers and patients and, consequently, a high degree of risk and workload. Hospital Hygiene and Cleaning Services play an important role in the effectiveness of the services provided in the sector, as well as for the management of individual and collective health and safety. By undressing the actual work from ergonomic and ergonomic approaches, this study sought to understand the activity of the employees of hygiene and cleaning services, the (in)visibility of the risks present in the sector and the importance of (re)knowledge of regulatory strategies in the face of the variability present in such a complex work environment. Through a descriptive qualitative study, it was possible to raise the perception of work of the research participants as well as the importance of their performance for quality and safety in the sector. It was evidenced that the performance of workers for local management is extremely important, even if daily the work they perform and the risks with which they experience are not perceived by most of the users inserted there.